Matrix sustainable strategies compatibility analysis of Malaysia's sustainable development strategies in three-tier development plan system - Ponrahono, Zakiah; Che Omar, Che Musa; Abdullah, Ahmad Makmom; Muda, Azizi (IDOSI Publications, 2011)
Sustainable development is widely explained throughout the planning world as a very important approach in balancing the use of limited resources for future needs. One of the best endeavours to implement the theory and concept of sustainability is through the adoption in the development plan system. However, standard and precise sustainable assessment method is needed to evaluate the sustainability of strategies, policies, plans, programs and projects of development plan. Thus, in this study Matrix Sustainable Strategies Compatibility Analysis is developed and used to evaluate the integration of sustainable strategies formulated in Malaysia’s three-tier development plan system. National Physical Plan was selected as core reference in evaluating its compatibility with other national, state and local plan sustainable strategies. The result of assessment is significant to figure out the integration of development plan system and the importance of clear interpretation of sustainable strategies.